1998
DOI: 10.1007/s001270050057
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to utilization of services for mental health reasons in Montreal, Canada

Abstract: This study examines factors related to the utilization of services for mental health reasons by Montreal residents. Data were drawn from telephone interviews. A random sample of 893 respondents completed a questionnaire on service utilization and the Diagnostic Interview Schedule Self Administered to assess DSM-III-R psychiatric disorders. Results indicate that 12.8% of the population had used such services in the past year. Medical doctors and psychiatrists, whose services are free of charge under universal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
43
2
8

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 13 publications
12
43
2
8
Order By: Relevance
“…As with previous studies, respondents consulted mostly with a family physician for mental health reasons. 1,10,[42][43][44][45][46] The prevalence rates observed for past year service use for mental health reasons, as well as by provider type, were slightly lower than those reported in a recent study in the Joint Canada-US Survey of Health. 47,48 Regarding the breakdown of services used for mental health reasons, there seemed to be an equal number of respondents consulting only a family physician, a family physician and another professional, and a professional other than a family physician in the past year.…”
Section: Discussionmentioning
confidence: 99%
“…As with previous studies, respondents consulted mostly with a family physician for mental health reasons. 1,10,[42][43][44][45][46] The prevalence rates observed for past year service use for mental health reasons, as well as by provider type, were slightly lower than those reported in a recent study in the Joint Canada-US Survey of Health. 47,48 Regarding the breakdown of services used for mental health reasons, there seemed to be an equal number of respondents consulting only a family physician, a family physician and another professional, and a professional other than a family physician in the past year.…”
Section: Discussionmentioning
confidence: 99%
“…In our final analysis of health care usage by MDD or anxiety disorder subjects, no other sociodemographic factor other than living alone remained statistically significant. At least three previous studies [Lin et al, 1996;Lefebvre et al, 1998;Bijl and Ravelli, 2000] report higher service usage among single householders and unmarried people. Other studies have found either no such association [Sherbourne, 1988;Golding et al, 1990;Phillips and Murrell, 1994] or an increasing use of mental health services but not primary health services [Ten Have et al, 2002].…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…However, it is similarly well established by epidemiological studies worldwide that about half of the subjects suffering from severe forms of these disorders and more than half of those with moderate or mild disorders do not seek or receive treatment from health services . Previous studies [Leaf et al, 1988;Bassett et al, 1998;Lefebvre et al, 1998;Ten Have et al, 2002] have suggested that severity of the psychiatric symptoms, psychiatric comorbidity, available resources, and different health behavior patterns influence seeking treatment. Also, different sociodemographic factors may have an influence on help-seeking [Olfson and Klerman, 1992;Crow et al, 1994;Lin and Parikh, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…This literature suggests that co-morbidity, general use of healthcare, salience of symptoms, deviance of symptoms, and interference with daily life predict helpseeking for conditions as diverse as psychological problems (Lefebvre, Lesage, Cyr, Toupin, & Fournier, 1998), pre-menstrual syndrome (Robinson & Swindle, 2000), urinary incontinence (Hannestad, Rortveit, & Hunskaar, 2002), and brain tumors (Salander, Bergenheim, Hamberg, & Henrikkson, 1999). Finally, as theory suggests, social network support (Carpentier & White, 2002) and especially spousal support (Salander et al, 1999) are related to helpseeking.…”
Section: Prior Researchmentioning
confidence: 99%